Spermidine Increases the Sucrose Content in Inferior Grain of Wheat and Thereby Promotes Its Grain Filling - Luo, Jian; Wei, Bin; Han, Juan; Liao, Yuncheng; Liu, Yang (Frontiers in Plant Science, 2019)
The improvement of grain filling is the key issue for promoting wheat grain weight and grain yield. Polyamines (PAs) significantly affect grain filling in cereals, but the mechanism by which PAs affect grain filling in wheat is unclear. In the present study, six wheat cultivars whose grain filling differed were used, and their grain-filling characteristics and endogenous PA contents were measured. In addition, exogenous PAs were supplied during the wheat grain-filling period. The grain-filling characteristics, hormone levels, starch contents and gene expression (based on RNA sequencing (RNA-seq)) in the grain were analyzed. The objective of the present study was to investigate the effects of PAs on grain filling in wheat. The results suggested that the direct synthetic pathway from putrescine (Put) to spermidine (Spd) in the grain was a key factor in promoting grain filling and grain weight in wheat. Spd through regulates the grain-filling rate of inferior grain during the early grain-filling period to affecting the grain filling and grain weight of wheat. The promotive effect of Spd on the grain filling of inferior wheat grain was notably related to carbohydrate metabolism in that grain. Spd significantly increased the zeatin (Z) + zeatin riboside (ZR) contents but reduced the ethylene (ETH) evolution rate in the inferior grain. In addition, Spd significantly increased the sucrose synthase (SS) and acid invertase (AI) activities in the inferior grain. These effects of Spd led to increased sucrose content in the inferior grain. These reasons might explain why Spd significantly promoted the filling and weight of inferior wheat grain.